Myeloid but not epithelial tissue factor exerts protective anti‐inflammatory effects in acid aspiration‐induced acute lung injury. (20th June 2017) - Kral‐Pointner, J. B.; Schrottmaier, W. C.; Horvath, V.; Datler, H.; Hell, L.; Ay, C.; Niederreiter, B.; Jilma, B.; Schmid, J. A.; Assinger, A.; Mackman, N.; Knapp, S.; et al.
Abstract : Essentials Tissue factor (TF) represents a central link between hemostasis and inflammation. We studied the roles of myeloid and airway epithelial TF in acid‐caused acute lung injury (ALI). TF on myeloid cells displays a non‐coagulatory role regulating the inflammatory response in ALI. Airway epithelial TF contributes to hemostatic functions, but is dispensable in ALI pathogenesis. Summary: Introduction: Acute lung injury (ALI) is a life‐threatening condition characterized by damaged alveolar–capillary structures and activation of inflammatory and hemostatic processes. Tissue factor (TF) represents a crucial link between inflammation and coagulation, as inflammatory mediators induce myeloid TF expression, and TF initiates extrinsic coagulation. Objective: As pulmonary inflammation stimulates TF expression and TF modulates immune responses, we aimed to elucidate its impact on ALI. In particular, we wanted to distinguish the contributions of TF expressed on airway epithelial cells and TF expressed on myeloid cells. Methods: Mice with different cell type‐specific TF deficiency and wild‐type littermates were intratracheally treated with hydrochloric acid, and leukocyte recruitment, cytokine levels, thrombin–antithrombin (TAT) complexes and pulmonary protein‐rich infiltrates were analyzed. Results: Our data demonstrate that a lack of epithelial TF did not influence acute responses, as bronchoalveolar neutrophil accumulation 8 h after ALI induction was unaltered. However, it led to mild, prolonged inflammation, as pulmonary leukocyte and erythrocyte numbers were still increased after 24 h, whereas those in wild‐type mice had returned to basal levels. In contrast, myeloid TF was primarily involved in regulating the acute phase of ALI without affecting local coagulation, as indicated by increased bronchoalveolar neutrophil infiltration, pulmonary interleukin‐6 levels, and edema formation, but equal TAT complex formation, 8 h after ALI induction. This augmented inflammatory response associated with myeloid TF deficiency was confirmed in vitro, as lipopolysaccharide‐stimulated TF‐deficient alveolar macrophages released increased levels of chemokine (C‐X‐C motif) ligand 1 and tumor necrosis factor‐α as compared with wild‐type macrophages. Conclusion: We conclude that myeloid TF dampens inflammation in acid‐induced ALI.